Community Education and Resilience: Making Knowledge, Making Community - Klara Kozar Rosulnik; Mojca Blažič; Petra Javrh; Nives Ličen (Changing Societies & Personalities)
This exploratory qualitative study focuses on the importance of community education in fostering community resilience. The research is grounded in a conceptual framework that encompasses resilience, well-being, and community education. The data were collected in Slovenia between 2020 and 2022 through two cycles based on the principles of participatory qualitative research involving 18 community education actors. Semi-structured interviews and participant observation were employed. A thematic content analysis of the interviews identified key themes and categories. Additional anecdotal data were gathered through participant observation in three selected community organizations and informal conversations with program providers, such as teachers. These anecdotal data served as a means of source triangulation and category validation. The findings indicated that community education enhances resilience and cohesion through knowledge co-creation, the development of social and emotional well-being, motivational programs, and emancipatory engagement. It empowers communities to build their capacity to respond to unpredictable challenges. The participants emphasized the need to develop new forms of community education, characterized as a pedagogy of contingency.